2024
DOI: 10.1021/acs.est.3c08046
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Fate and Roles of Dissolved Organic Matter from Spatially Varied Grassland Soils in China During Long-Term Biogeochemical Processes

Peng Zhou,
Long Tian,
Muhammad Saboor Siddique
et al.

Abstract: Terrestrial dissolved organic matter (DOM) is critical to global carbon and nutrient cycling, climate change, and human health. However, how the spatial and compositional differences of soil DOM affect its dynamics and fate in water during the carbon cycle is largely unclear. Herein, the biodegradation of DOM from 14 spatially distributed grassland soils in China with diverse organic composition was investigated by 165 days of incubation experiments. The results showed that although the high humified fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
0
0
Order By: Relevance
“…These results were consistent with the FTIR, XPS, and CLSM analysis and further confirmed that the Fe­(OH) 3 /GO membrane can reduce the accumulation of EPS and alleviate biofilm formation. Furthermore, the lower ratio of humic-like to protein-like substances for the Fe­(OH) 3 /GO compared with the other two membranes suggested that organic matter within the Fe­(OH) 3 /GO biofilm had higher biodegradability . In addition, the organic matter in different biofilms also exhibited distinctions in molecular size, type and degree of aromatic rings substitution, and ζ potential, highlighting the complexity of biofilm organic matter (SI, Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with the FTIR, XPS, and CLSM analysis and further confirmed that the Fe­(OH) 3 /GO membrane can reduce the accumulation of EPS and alleviate biofilm formation. Furthermore, the lower ratio of humic-like to protein-like substances for the Fe­(OH) 3 /GO compared with the other two membranes suggested that organic matter within the Fe­(OH) 3 /GO biofilm had higher biodegradability . In addition, the organic matter in different biofilms also exhibited distinctions in molecular size, type and degree of aromatic rings substitution, and ζ potential, highlighting the complexity of biofilm organic matter (SI, Figure S11).…”
Section: Resultsmentioning
confidence: 99%